THE EFFECT OF PHYSICAL EXERCISE ON QUALITY OF LIFE DURING PREGNANCY - Ksenija Bubnjević; Jelena Kovačević (Exercise and Quality of Life)
Pregnancy is a physiological condition during which a series of morphological and anatomicalchanges occur. Adaptation to new changes in the body depends on the psychological andphysical condition of the patient. One of the many factors that affect the quality of life is physicalexercise. Proper exercise prevents certain chronic diseases, reduces pregnancy discomfort, givesa feeling of satisfaction and influences a positive outcome of the pregnancy. The aim of thisstudy was to examine the validity of the preliminary version of the questionnaire, and thereforeexamine the impact of exercise on the quality of life during pregnancy. The questionnaireinvolved pregnant women (N=33). All of whom were in their third trimester of pregnancy. Theparticipants voluntarily filled out an anonymous questionnaire. The questionnaire includedinformation about: social and marital status, education, frequency of maternity problems, thetype of exercise, as well as the level of training load during pregnancy. High reliability andvalidity of the survey (0,873) was determined by Cronbach alpha coefficient. Pregnant women(48%) commonly practiced low intensity yoga, up to three times a week. Most of the women(45%) believe that the exercise has a positive impact on their health. A difference of statisticalsignificance was observed between the type of exercise and heart burn (r=0.349; p=0.046), aswell as between the type of exercise and body weight (r=0.357; p=0.041). The results of thispilot study show a lower incidence of common maternity symptoms in pregnant women whoexercised during pregnancy.